JavaSoft cooking up some next-generation JavaBeans - Scannell, Ed; Cunningham, Cara (InfoWorld, 1997)
JavaSoft is lining up features for the next 2 generations of its JavaBeans specification. This summer's JavaBeans update, code-named Glasgow, will likely introduce an aggregation and delegation model that will make it easier for developers to glue various JavaBeans together to create applications. JavaSoft is stressing that Glasgow, as well as its 1998 successor, code-named Edinburgh, are under investigation and subject to change. Glasgow will let developers add data typing and registry functions to JavaBeans. Edinburgh's tentative features include a composite interface for embedding a user interface into a JavaBeans component.